Prenatal diagnosis of haemophilia B: the Italian experience. (28th June 2013) - Belvini, D.; Salviato, R.; Acquila, M.; Bicocchi, M. P.; Frusconi, S.; Garagiola, I.; Sanna, V.; Santacroce, R.; Rocino, A.; Tagariello, G.
Summary: This article describes prenatal diagnosis (PND) of haemophilia B (HB) within the framework of Italian haemophilia centres and genetics laboratories. The study details the experience from six haemophilia genetic centres (three in the North, one in the Centre and two in the South of Italy) and summarizes the different techniques used to perform PND of HB during the last 15 years. To date, the Italian HB database includes 373 characterized unrelated patients and their genetic information has permitted the identification of 274 carriers of childbearing age. This database represents the main instrument for timely and precise PND. Sixty‐six prenatal diagnoses were performed on 52 HB carriers whose average age at the time was 34 (ranging from 24 to 44 years). In 44 cases, genetic counselling for carrier status determination was performed before pregnancy, while eight were not studied prior to pregnancy. Foetal samples were obtained by chorionic villus sampling in 52 cases, by amniocentesis in 12 while two were diagnosed by analysis of free foetal DNA obtained from maternal peripheral blood. In 35 (53%) pregnancies the foetus was female. For 31 men (47%), haemophilia status was determined by analysis of previously determined informative markers or familial mutations (12 affected and 19 unaffected). There may be more than one laboratory involved in the PND diagnostic pathway (providing DNA extraction, karyotype analysis, gender determination, maternal contamination detection, molecular diagnosis and sequencing). Good communication between all the parties, coordinated by the haemophilia centre, is essential for a successful and rapid process.